2014
DOI: 10.1007/s12040-014-0456-6
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake source characteristics along the arcuate Himalayan belt: Geodynamic implications

Abstract: The occurrences of moderate to large magnitude earthquakes and associated subsurface geological processes were critically examined in the backdrop of Indian plate obliquity, stress obliquity, topography, and the late Tertiary regional tectonics for understanding the evolving dynamics and kinematics in the central part of the Himalayas. The higher topographic areas are likely associated with the zones of depressions, and the lower topographic areas are found around the ridges located in the frontal part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 124 publications
0
8
0
Order By: Relevance
“…Epicentres of historical damaging earthquakes predominantly concentrated in the area of clustered seismicity ( Figure 1). An earlier study 2 reported that the seismic activities are apparently confined in some specific segments along the arc as noted in Figure 1. Depth-section study indicates (Figure 2).…”
Section: Tectonic Frameworkmentioning
confidence: 81%
See 1 more Smart Citation
“…Epicentres of historical damaging earthquakes predominantly concentrated in the area of clustered seismicity ( Figure 1). An earlier study 2 reported that the seismic activities are apparently confined in some specific segments along the arc as noted in Figure 1. Depth-section study indicates (Figure 2).…”
Section: Tectonic Frameworkmentioning
confidence: 81%
“…Segment-specific seismic activities 1,2 , rotational underthrusting and concomitant uneven southward migration of the Asian crust 3,4 , along-strike wide variation of the Indian plate obliquity (Figure 1), and occurrence of seismicity in the mantle-lithosphere of the Indian plate 5 clearly account for lateral changes in the dynamics/kinematics of the Himalaya. Although several studies involving gravity modelling were carried out for Nepal-Sikkim Himalaya [6][7][8][9][10][11][12][13] , the present study analyses the Bouguer gravity anomaly along a strike-orthogonal profile passing through the epicentre of the 7.9 magnitude Nepal earthquake for a detailed understanding of the spatial distribution of its aftershocks and other great shocks in this part of the Himalaya ( Figure 2).…”
mentioning
confidence: 99%
“…The development of the deformation zone in the north‐eastern Indian Ocean is reported to have been initiated in the Early Miocene at 18–14 Ma (Bull, DeMets, Krishna, Sanderson, & Merkouriev, ; Krishna et al, ). The active resistance during underthrusting of the Indo‐Australian Plate along the Himalayan boundary initiated the reverse transmission of a compressive stress field within the plate interior, which accounts for the occasional incidences of great intraplate earthquakes (Aggarwal, Khan, Mohanty, & Roumelioti, ; Khan, Ansari, & Mohanty, ; Khan, Mohanty, Sinha, & Singh, ) and the neotectonic activities (Biswas, ). The deformation of the Indo‐Australian lithosphere, unconformity in the floor of the Bay of Bengal, concomitant folding and faulting in the equatorial Indian Ocean, and the lateral evolutions of basins and ridges near the foothills of the Himalayas are the tectonic responses that evolved during the Oligocene‐Miocene time (Ansari & Khan, ; Cochran, ; Curray, ; Gordon, , and references therein).…”
Section: Tectonics Set‐upmentioning
confidence: 99%
“…2005; Jessup et al 2008;Jessup and Cottle 2010;Hintersberger et al 2010;Langille et al 2010;Saylor et al 2010;Styron et al 2011;Xu et al 2013;Nagy et al 2015). Comparatively, reports on arc-parallel compression from the Himalaya are less (e.g., Zeitler 1985;Treloar et al 1991;Llana-Fúnez et al 2006;Shah et al 2011;Khan et al 2014;Banerjee et al 2015;Sayab et al 2016). Interestingly, such compression has also been reported from other collisional orogens, e.g., the Indo-Myanmar range (Parameswaran and Rajendran 2016), the Alps (Peresson and Decker 1997), the Andes (Boutelier and Oncken 2010;Johnston et al 2013), the Apennine (Carosi et al 2002;Viti et al 2004;Bonini et al 2011), the Cascadia (Wang and He 1999), the Hellenic Arc (Konstantinou et al 2006) and the Variscan (Johnston et al 2013;Weil Viti et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Few models explain arc-parallel compression in terms of simultaneous compression and micro-plate rotation (Apennine; Viti et al 2004), cessation of subduction retreat (Alps; Peresson and Decker 1997), lower flexural rigidity of downgoing lithosphere and/or high interplate friction (Andes; Boutelier and Oncken 2010), curved subduction zone (Hellenides; Durand et al 2014 and references therein) and an orthogonal switch in the stress field (Variscan;Johnston et al 2013;Del Greco et al 2016). The Himalayan arc-parallel compression can be an outcome of either (i) strain concentration at the NW and the NE bends of the Himalayan thrusts (close to the syntaxes) (Treloar et al 1991;Seeber and Pêcher 1998) or (ii) an increase in plate obliquity coupled with an increase in the arc-parallel shear away from the central Himalaya and towards the syntaxes, due to the India-Asia convergence (Khan et al 2014). Moreover, Upton et al (2008) suggested that oblique ramps can also cause a rotation of the principal stress axes.…”
Section: Introductionmentioning
confidence: 99%